Benefits and Quality of Life Outcomes From Transportation Voucher Use by Adults With Disabilities. Issue 4 (December 2013) - Samuel, Preethy S.; Lacey, Krim K.; Giertz, Chesley; Hobden, Karen L.; LeRoy, Barbara W.
Abstract People with disabilities often feel isolated from their communities, which in turn affects their emotional well‐being and their overall quality of life. Access to transportation is a substantial barrier to community participation and an improved quality of life for individuals with disabilities. Transportation voucher programs represent a cost‐effective way to provide access to transportation for people with disabilities, but few studies have empirically examined the effectiveness of such programs. The present study examined the perceived benefits of participating in a transportation voucher program in Michigan, a midwestern state in the United States with limited public transportation. Cross‐sectional survey data collected from a convenience sample of 73 participants of the transportation voucher program, funded by the state's Developmental Disabilities Council from 2005 to 2008, were analyzed. Participation outcomes were differentiated by age, sex, employment status, and type of disability using multivariate logistic regression analysis. More than two‐thirds (70%) of participants reported that their emotional well‐being and community participation had improved, and 54% of participants indicated that participation in the voucher program had resulted in better overall quality of life. The type of disability was an important factor in determining the degree of gain experienced, particularly in terms of community participation and overall quality of life. Findings suggest that resources spent on developing voucher programs have the potential to enrich the lives of persons with disabilities and their families. However, future longitudinal research along with a comparison group may be necessary to validate these preliminary findings on the benefits of vouchers.